Facile synthesis of porous-structured nickel oxide thin film by pulsed laser deposition - Jahromi, S.P.; Huang, N.M.; Kamalianfar, A.; Lim, H.N.; Muhamad, M.R.; Yousefi, R. (Hindawi Publishing Corporation, 2012)
Porous-structured nickel oxide (PsNiO) was obtained through the oxidization of a nickel thin film. The nickel thin film was deposited using the pulsed laser deposition (PLD) method on a nickel foil as a substrate. The results show uniform PsNiO after the oxidization of the nickel thin film at 750 degrees C for 1 h. X-ray diffraction (XRD) indicates formation of the NiO crystalline structure. Field emission scanning electron microscopy (FESEM) reveals different morphology on the surface of the nickel foil (sample A) and on the nickel thin film (sample B). Comparison of the FESEM results after oxidization shows that the PsNiO on the nickel thin film was more regular and controllable than the NiO layer on the nickel foil. The FESEM images also show that the thickness of the nickel thin film affected the PsNiO size obtained after oxidization. This resulted from the growth of the porous structure at grain boundaries and from the grain sizes. The electrochemical properties of the PsNiO as an electrode are investigated by cyclic voltammetry (CV). These results show the effect of PsNiO size on the current of anodic peak.